Activation of Checkpoint Kinase Chk1 by Reactive Oxygen Species Resulting from Disruption of wat1/pop3 in Schizosaccharomyces pombe. Issue 4 (1st December 2016) - Ahamad, Nafees; Verma, Sumit Kumar; Ahmed, Shakil
Abstract: DNA double-strand breaks are critical lesions that can lead to chromosomal aberrations and genomic instability. In response to DNA damage, Chk1, a serine/threonine kinase, is responsible for cell cycle arrest to prevent damaged cells from progressing through the cell cycle. Here, we report that the disruption of wat1, a WD repeat-containing protein, leads to the phosphorylation of Chk1. The double-deletion of chk1 and wat1 had a grave effect on the survival of fission yeast cells, and the spontaneous recombination rate was also high upon double-deletion of wat1 and chk1, as compared to the single-mutant. In the absence of wat1, the cells exhibited a high level of nuclear fragmentation that resulted in the accumulation of Rad22 yellow fluorescent protein foci. Furthermore, we show that wat1 is required for the regulation of the oxidative stress response. We observed elevated levels of reactive oxygen species (ROS) generation in wat1 -null mutant that led to a high degree of propidium iodide staining at nonpermissive temperature. Based on the results presented here, we hypothesize that ROS production in wat1 -null mutant cells generates DNA fragmentation that could trigger a checkpoint response and that, in the absence of checkpoint kinase Chk1, the cells exhibit severe growth defects leading to a synthetic lethal phenotype.